2021
DOI: 10.1007/s10815-020-02056-2
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive prenatal detection of fetal sex chromosome abnormalities using the semiconductor sequencing platform (SSP) in Southern China

Abstract: Background Noninvasive prenatal testing (NIPT) has been widely used to screen for fetal aneuploidies, including fetal sex chromosome aneuploidies (SCAs). However, there is less information on the performance of NIPT in detecting SCAs. Methods A cohort of 47,800 pregnancies was recruited to review the high-risk NIPT results for SCAs. Cell-free fetal DNA (cffDNA) was extracted and sequenced. All NIPT high-risk cases were recommended to undergo invasive prena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
1
2
1
Order By: Relevance
“…Consistent with previously reported studies, PPV for 45,X was much lower than that for other SCAs in this study [ 1 , 5 , 13 , 15 , 16 ]. Several factors contributed to the poorer performance of NIPT in screening for monosomy X as opposed to trisomies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with previously reported studies, PPV for 45,X was much lower than that for other SCAs in this study [ 1 , 5 , 13 , 15 , 16 ]. Several factors contributed to the poorer performance of NIPT in screening for monosomy X as opposed to trisomies.…”
Section: Discussionsupporting
confidence: 93%
“…PGT-A is widely used to detect aneuploidy in embryos to improve implantation rates after IVF, and some studies have reported that it can reduce aneuploidy and miscarriage rates [ 44 , 45 ]. Interestingly, 26.19% (2,403 women) enrolled in this study were IVF pregnancies, showing a much higher proportion than that of other studies (5.9%, 2.66%, and 10.0%) [ 16 , 17 , 31 ]. Among these, 5.99% (144 women) had undergone PGT-A, implying that more aneuploidy might have preemptively filtered out via PGT-A before NIPT screening.…”
Section: Discussioncontrasting
confidence: 56%
“…In some cases of SCA, there is often no obvious clinical phenotype in the fetus, and ultrasound does not show obvious abnormalities, so follow-up in the fetus and infancy does not reveal phenotypic abnormalities, and only after puberty does it cause serious physical and psychological effects. Therefore, prenatal screening, genetic counseling and long-term follow-up of SCA are particularly important [ 21 ], in addition, low fetal fraction is an important reason for the limitations of NIPT testing. Maternal age, weight, gestational age, tumor, and fetal placental mosaicism all influence fetal fraction, and there is wide variation among individuals.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of reports have proven that NIPT is the most accurate screening test for trisomy 21, trisomy 18, and trisomy 13 with high sensitivity and specificity ( 9 22 ). However, limited studies have evaluated the accuracy of NIPT for screening SCAs ( 7 , 8 , 23 ). Therefore, we investigated the application of MPS-based NIPT for screening of SCAs among pregnant women in our center in central China.…”
Section: Introductionmentioning
confidence: 99%